Mobile IPTV: Implications for Education - Suanpang, Pannee (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Mobile IPTV (Internet Protocol Television) provides digital content which users watch as a television broadcast via the Internet on a mobile device. This paper presents the development of IPTV, Suan Dusit Internet Broadcasting, (SDIB) to mobile IPTV and discusses the implications for education. Mobile IPTV was developed as a prototype and designed to support users via wireless and mobile networks regardless of the mobile device. The system can be broadcasted through both live and video on demand (VOD) utilizing a mobile browser (smart phones, smart TVs, and tablets) and web browsers (Windows, Mac, and UNIX). The mobile IPTV prototype has been used and evaluated in this study. The results of student’s behavior when using mobile phones in their learning found that the highest mobile use was for Facebook and Line to communicate and share information with their classmates. The results of student’s attitudes towards using mobile phones in their learning found that the highest mobile use was for sharing information with classmates, sharing learning experiences on social networks, and using mobile phones to support their studies. The result of the IPTV and mobile IPTV system evaluation found that overall mobile IPTV had a higher user satisfaction than IPTV. Furthermore, mobile IPTV creates a good learning experience for the users. This paper provides guidelines in technical issues for helping educational institutions to develop mobile IPTV for education.